Power system operation control and restructuring - Gupta, S. K. (New Delhi, India : I.K. International Publishing House Pvt. Ltd., 2015)
This book is an attepmt to understand how to arrange reliable, secure, stable power in competitive environment. Load frequency control is essential for successful opeation of power systems, especially interconnected power systems. The book includes topics such as optimal dispatch, load flow studies, state estimations, fault analysis, automatic generation control, excitation control, stability, modeling of power components, HVAC & FACTS, restructuring power systems.
load flow analysis-- optimal load dispatch-- short circuit studies-- modeling-- supervisory control and data acquisition-- restructuring power system-- automatic generation control-- power system stability-- excitation, voltage stability and control-- extra high voltage transmission and FACTS-- the leas, challenges and issues in competitive market
Includes index.
Keywords: ELECTRIC POWER SYSTEMS -- INDIA -- CONTROL